Prevalence, Patient Characteristics, and Treatment of Patients with Hypertrophic Cardiomyopathy: A Nationwide Payer Database Study - Yuika Ikeda; Tsunehisa Yamamoto; Makio Torigoe; Bruno Casaes Teixeira; Thomas Laurent (Cardiology and Therapy)
Abstract Introduction Data on the prevalence of hypertrophic cardiomyopathy (HCM), characteristics of patients with HCM, and treatment patterns in Japan are limited. This study aimed to estimate the prevalence of HCM and describe the patient characteristics, treatment patterns, and utilization of medical expense subsidies in Japan, using payer claims data from insurers. Methods This retrospective study of patients with HCM in Japan utilized payer claims data from insurers (Advanced Elderly Medical Service System [AEMSS], Kokuho, and Kempo) from January 1, 2017, to December 31, 2021. The prevalence of HCM was calculated annually; while medication use, comorbidities, and usage of medical expense subsidies were described for 2021 as representative data. Results The estimated prevalence of HCM increased from 9.3/10,000 people in 2017 to 11.1/10,000 people in 2021. In 2021, the highest prevalence was observed in patients aged 85–89 years (39.0/10,000 people). For patients with HCM, mean (standard deviation) age was 82.5 (5.5) years (AEMSS), 66.7 (9.2) years (Kokuho), and 53.4 (14.0) years (Kempo). Hypertension was the most common comorbidity (AEMSS, 90.7%; Kokuho, 85.7%; Kempo, 71.4%), followed by heart failure (AEMSS, 77.3%; Kokuho, 64.4%; Kempo, 56.9%). Mental health disorders were reported in 22.4% (AEMSS), 16.3% (Kokuho), and 11.3% (Kempo) of patients with HCM. Beta-blockers were the most frequently prescribed medications (AEMSS, 65.1%; Kokuho, 63.2%; Kempo, 56.6%). A small proportion of patients whose HCM was diagnosed in 2021 received medical expense subsidies (AEMSS, 2.6%; Kokuho, 4.6%). Conclusions This study is the first to evaluate the prevalence of HCM in Japan using data from the general population as the denominator. It indicated that patients with HCM are typically > 50 years old, have a high prevalence of comorbidities, are commonly treated with beta-blockers, and rarely receive medical expense subsidies for designated intractable diseases. About one-fifth of the patients had mental health disorders.